Peran Academic Buoyancy terhadap Engagement dalam Aktivitas Belajar Jarak Jauh di Perguruan Tinggi - Veronica Brigitha; Meilani Rohinsa (Universitas Kristen Maranatha, 2023)
The Covid-19 pandemic has forced many activities to adjust, including educational institutions. Distance learning situations need students who can be actively involved in learning, creative in finding various learning resources, and independent learning, or what is known as Engagement. In terms of distance learning activities, students feel that it is a challenge and even an obstacle. It takes the ability to overcome it, or what is known as Academic buoyancy. This study aims to see how the role of Academic buoyancy on Engagement. Participants in this study were 252 students aged 18-22 years. The measuring tools in this study are the Engagement Questionnaire and the Academic Buoyancy Scale. The results of this study indicate that Academic buoyancy has a significant role in the emergence of student engagement in learning activities, especially when running distance learning. The results of this study imply the importance of training students to have the ability to overcome academic obstacles to be more involved in learning activities.